Persepsi Masyarakat Menentukan Partisipasi Dalam Vaksinasi Covid-19 : Studi di Desa Tanggulkundung Kecamatan Besuki Kabupaten Tulungagung. - Lenita Ansika Margarisa; Muhammad Taukhid; Didit Damayanti (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2022)
The Covid-19 vaccination program among the public raises various perceptions, both negative perceptions and positive perceptions, this affects community participation in participating in the Covid-19 vaccination which is supported by several factors such as gender, education, age, occupation, knowledge about the Covid-19 vaccine, cultural beliefs and vaccine history. This research aim to analyzed the correlation between public perception and participation for Covid-19 vaccination in Tanggulkundung Village, Besuki Sub-District, Tulungagung District. The design of this research used the correlation method with a cross-sectional approach. The population in this resrarch were 800 respondents with a sample of 89 community respondents in Tanggulkundung Village, Besuki, Tulungagung. The sampling technique used Purposive Random Sampling. Collecting data on the independent variable of public perception and the dependent variable on Covid-19 vaccination participation used a questionnaire. The results showed that most respondents (69.7%) had a positive perception and almost all respondents (94.4%) had a positive Covid-19 vaccination participation rate. The results of the statistical test of rho Spearman rank obtained p-value 0.002 (α<0.05), then H1 accepted with r = 0.324. The strength of this correlation is due to the intercorrelation between variables which are influenced by several factors, one of which is knowledge, so that additional information is needed from the Covid-19 vaccine to increase public knowledge so that it creates a positive perception. It is also recommended that the public can wisely digest the contents of any information circulating about the Covid-19 vaccine, it is hoped that the entire community can have the same perception and can increase participation in the Covid-19 vaccination.